Genotype-8: A Modern Family Member of Hepatitis C Virus - Gudi, Sai Krishna; Chhabra, Manik; Rashid, Muhammed (Indian Journal of Pharmaceutical Education and Research, 2019)
Hepatitis C Virus (HCV) is a highly diverse and pervasive disease around the globe, with a prevalence ranging from 1.5 to 2.3%. With wide genetic variability, it is classified into seven Genotypes (GT) with 67 subtypes. The sighting of a modern HCV GT-8 ratifies its endemic character in India, particularly in the Punjab State. Getting familiarized and making aware of the HCV genotypes and subtypes is necessarily essential in establishing the optimal treatment regimen.
Keywords: Hepatitis C; RNA virus; Epidemiology; Genotype Classification; Genotype 8; India